Corporate Liability in Banking Crimes under the PPSK Law: Between Legal Framework and Enforcement Challenges - Saragih, Jhon Feri Sariaman (Universitas Muhammadiyah Surabaya, 2025)
This research addresses the legal issue of corporate liability in banking crimes as regulated under Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (PPSK Law). The study aims to analyze the normative framework governing banking crimes committed by corporate legal subjects, particularly the absence of specific implementing regulations. The research employs a normative legal method, with the statute approach and conceptual approach as the main analytical tools. The findings show that, due to the lack of implementing provisions within the PPSK Law, Supreme Court Regulation Number 13 of 2016 concerning Procedures for Handling Criminal Cases by Corporations (PERMA Korporasi) remains applicable. This regulation provides procedural guidelines on examination, evidence, and technical aspects in cases where corporations are defendants, and therefore can be extended to corporate banking crimes.